Multiple Dimensions of Impoverishment in Iran - Mahoozi, Hosnieh; Meckl, Jürgen (Journal of Income Distribution®, 2020)
Concerning the demands of Sen’s (1984) Capability Approach to the assessment of human well-being, we estimate multidimensional poverty and compare the results with traditional measures of income poverty in Iran. We detect poverty in urban and rural Iran over 1999-2007, a period with relatively high GDP growth. The results reveal that the pace of income poverty reduction is much faster than the pace of multidimensional poverty alleviation. The pace of poverty reduction is much slower in rural areas than in urban areas and the capital city, Tehran. Hence, inequality between rural and urban areas increased over the time. We also show how policymakers may benefit from applying the multidimensional approach in targeting the subgroups by the most deprived aspects.